Content categories on Instagram: from promotional to interactivity for business development - Maulidian Maulidian; Salwa Fatima Zahra; Anys Tasya Nadela; Anisa Fitriani (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — The study aimed to analyze the content on Instagram and to examine the relationship between the content categories and the reach and impressions of the posts.Method — This study analyzed 58 content posts from the Instagram account @Generasi_kenzu using purposive sampling, divided into five categories and measured based on accounts reached and impressions, using descriptive statistics, a Kolmogorov-Smirnov test for normality, and a Kruskal-Wallis test for comparison of mean reach and impressions across the categories.Result — The content analysis revealed that promotion was the most prevalent category, followed by information and education, with a mean reach of 64.22 and a significant proportion of views from the user's profile, and found hashtags to be an effective method of increasing visibility, though with a considerable degree of variation among individual posts. The Kruskal-Wallis test showed no significant difference in the distribution of accounts reached, reach from follower, reach from non-follower, impressions, from profile, from hashtags, from home and from other across the five content categories.Contribution — This study contributes by adding knowledge about content categories' effectiveness on social media platforms, providing valuable insights into content and reach of Instagram posts, and suggesting the need for further research to explore impacting factors.